2006
DOI: 10.1002/path.1972
|View full text |Cite
|
Sign up to set email alerts
|

DC-SIGN association with the Th2 environment of lepromatous lesions: cause or effect?

Abstract: The clinical spectrum of leprosy is related to patients' immune responses. Non-responsiveness towards Mycobacterium leprae (ML) seems to correlate with a Th2 cytokine profile. The reason for such a polarized immune response remains unclear. The C-type lectin, DC-SIGN, expressed by subsets of dendritic cells (DCs) and macrophages, has previously been associated with Th2 responses. Here we show abundant DC-SIGN expression in lepromatous but not borderline tuberculoid leprosy, in both HIV-positive and HIV-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
0
27
1
Order By: Relevance
“…M. leprae have also been reported inside epidermal cells analysed by TEM (42,46) with bacteria inside a keratinocyte of the epidermis in a leproma.The expression of CD209 (DC sign) triggers the initial contact between DC and T cells by binding to ICAM-3 on T cells (47). It has been suggested that CD209, when induced on macrophages in multibacillary leprosy, contributes to the entry of mycobacteria into these cells(48). Our data show that only a few keratinocytes express CD209.…”
contrasting
confidence: 38%
“…M. leprae have also been reported inside epidermal cells analysed by TEM (42,46) with bacteria inside a keratinocyte of the epidermis in a leproma.The expression of CD209 (DC sign) triggers the initial contact between DC and T cells by binding to ICAM-3 on T cells (47). It has been suggested that CD209, when induced on macrophages in multibacillary leprosy, contributes to the entry of mycobacteria into these cells(48). Our data show that only a few keratinocytes express CD209.…”
contrasting
confidence: 38%
“…Man-LAM has also been shown to bind the DC-specific ICAM-3-grabbing nonintegrin (DC-SIGN), a C-type lectin on DC and macrophages (32), and to interfere with TLR-mediated DC maturation (33). Interestingly, increased DC-SIGN expression in M. leprae-infected DCs has been recently described in L-lep vs T-lep patients (34). This report and a second one (35) showed that DC-SIGN acts as an entry receptor for M. leprae, much the same as has been described for M. tuberculosis (32,36).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that CD209 expression on Schwann cells is involved in the binding to M. leprae. Based on previous studies, it is likely that CD209 is interacting with Man-LAM (i.e., mannose-capped lipoarabinomannan) present in the M. leprae cell wall (9,30). In addition to recognizing mycobacteria, CD209 recognizes HIV and may contribute to AIDS pathogenesis, including HIV infection of peripheral nerve Schwann cells (13,31).…”
Section: Discussionmentioning
confidence: 99%
“…Among these is the C-type lectin receptor, CD209, also known as DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin), which mediates recognition of several pathogens, including viruses, fungi, and bacteria (8). CD209 facilitates cell binding to several species of mycobacteria, including M. tuberculosis, M. bovis, and M. leprae (9,20,30). The recognition of mycobacteria by CD209 has been shown to be mediated by interaction with the mycobacterial mannose-capped lipoarabinomannan (Man-LAM) (9).…”
mentioning
confidence: 99%